2012
DOI: 10.1128/jb.05911-11
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of β-Galactosidase Paralogues of the Rumen Bacterium Mannheimia succiniciproducens

Abstract: Mannheimia succiniciproducens, a rumen bacterium belonging to the family Pasteurellaceae, has two putative ␤-galactosidase genes, bgaA and bgaB, encoding polypeptides whose deduced amino acid sequences share 56% identity with each other and show approximately 30% identity to the Escherichia coli gene for LacZ. The M. succiniciproducens bgaA (MsbgaA) gene-deletion mutant was not able to grow on lactose as the sole carbon source, suggesting its essential role in lactose metabolism, whereas the MsbgaB gene-deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Overall, the MG group contained more families of GHs, including beta-galactosidase (GH2), alpha-L-fucosidase (GH95), and beta-glucosidase (GH3, GH97, and GH51) for converting cellobiose, as well as enzymes for UDP-GlcNA (GT41), acetyl xylan esterase (CE1), and arylesterase (CE10). Yaks in the MG group may have a greater ability to break down cellulose and hemicellulose, as beta-glucosidase not only hydrolyzes lactose but also plant polysaccharides catalyzed by microbial cellulases ( Lee et al, 2012 ). Previous studies have shown the importance of β-glucosidases, specifically GH3, GH51, and GH97, in converting cellobiose to enhance cellulose hydrolases ( Chen H. L. et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the MG group contained more families of GHs, including beta-galactosidase (GH2), alpha-L-fucosidase (GH95), and beta-glucosidase (GH3, GH97, and GH51) for converting cellobiose, as well as enzymes for UDP-GlcNA (GT41), acetyl xylan esterase (CE1), and arylesterase (CE10). Yaks in the MG group may have a greater ability to break down cellulose and hemicellulose, as beta-glucosidase not only hydrolyzes lactose but also plant polysaccharides catalyzed by microbial cellulases ( Lee et al, 2012 ). Previous studies have shown the importance of β-glucosidases, specifically GH3, GH51, and GH97, in converting cellobiose to enhance cellulose hydrolases ( Chen H. L. et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%